2005
DOI: 10.1038/sj.leu.2403972
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for involvement of clonally expanded CD8+ T cells in anticancer immune responses in CLL patients following nonmyeloablative conditioning and hematopoietic cell transplantation

Abstract: We have analyzed the clonotype composition of CD8 þ T cells following nonmyeloablative (NMA) conditioning and hematopoietic cell transplantation (HCT), of patients with chronic lymphocytic leukemia (CLL). Consecutive analyses of blood samples taken up to 2 years following HCT, demonstrated that CD8 þ T-cell clonality was highly dynamic in the early phases after HCT, but became more stable after 4-5 months. Moreover, donor lymphocyte infusion (DLI) given for disease progression in one of the patients led to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…These cells killed recipient CLL cells in vitro. Kollgaard et al 49 analyzed the clonotype of CD8-T-cells following RIC allotransplants. They showed that an early dynamic phase is followed by the appearance of stable T-cell clonotypes several months after transplant coinciding with clinical anti-leukemia response.…”
Section: T-cell Responses After Allotransplantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells killed recipient CLL cells in vitro. Kollgaard et al 49 analyzed the clonotype of CD8-T-cells following RIC allotransplants. They showed that an early dynamic phase is followed by the appearance of stable T-cell clonotypes several months after transplant coinciding with clinical anti-leukemia response.…”
Section: T-cell Responses After Allotransplantsmentioning
confidence: 99%
“…There are several reports of eradication of persistent and/or recurrent CLL after transplant. 18,[20][21][22]28,30,[41][42][43][44][45][46][47][48][49][50][51][52] Most report small numbers of subjects; only two had more than 10. 21,28 Overall, 43 of 92 subjects responded; 35 achieved complete remission and eight partial remission.…”
Section: Donor Lymphocyte Infusionsmentioning
confidence: 99%
“…Naturally occurring T cells recognizing leukemic cells have been previously described in CLL and play a role in controlling CLL [3,4]. Allogeneic T-cells in haematopoietic stem cells transplants or administered as donor lymphocyte infusions are known to mediate 'graft-versusleukaemia' effect which can effectively eradicate leukaemic cells [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, at least concerning patient 766, absence of HY-A2 reactivity was concurrent with significant overall reactivity. 11 Reactivity, in the context of HLA-B7 could potentially be relevant; 16 however, none of the patients expressed this HLA molecule (Table 1).…”
mentioning
confidence: 99%
“…The dextramer analyses of peripheral blood mononuclear cells from UPN 766 showed that only 0.2% of CD8 þ T cells (compared to approximately 10% being CD107a CD8 þ T cells upon CLL stimulation), were specific for HY in HLA-A2 context. 11 We, therefore, analyzed male patients that received HLAidentical NMA-HCT from their female sibling. To facilitate comparative studies, patient/donor pairs should be HLA-A2 positive and be characterized by parity for HA-1, HA-2 and HA8Fall of which give rise to HLA-A2 restricted peptides that might be dominant over HY.…”
mentioning
confidence: 99%